Analysis of the mechanism of state regulation of innovative projects in the regions of the Republic of Kazakhstan. - Mukhtarova Myltykbayeva Asanova, K. A. A. K. S. D. (Journal of Economic Research & Business Administration, 2016)
The main priority areas of science in Almaty is possible to determine areas such as nuclear science, biomedical science and technology research in the field of natural resources, agricultural science and technology, environmental protection and others. Innovative development of economy of the country is now the basis of the state policy of Kazakhstan, which is aimed at creating the economic conditions for production of competitive high-tech products. This article analyzes the mechanism of state regulation of innovative projects in the regions of Kazakhstan. To better support the new policy, the State should take the example of the benefits provided by the industrialized countries. Also believes that instruments to support innovation activities include tax incentives for activities of regional technology parks and EPZs. region; innovation; design innovation; government regulation